Induced mutation breeding through acute and chronic gamma irradiation for improvement of yield and quality traits of chili (Capsicum annuum L.) - Mohammedelnour, Aisha Awadalla Hashim (2020)
Chili (Capsicum annuum L.) is mainly cultivated in Malaysia for its high domestic consumption and market potential. In Malaysia, chili production is hindered by low yield and mostly susceptible to pests and diseases, hence, the country relies on importation to complement local production. Therefore, varietal development of highyield with resistant to major diseases is required to overcome this problem. On the basis of this prevailing situation, the present induction mutation breeding program was conducted to explore the possibility of inducing desirable variability for quantitative and qualitative traits on two inbred chili varieties (Chili Bangi 3 and Chili Bangi 5) using acute and chronic gamma irradiations. The main objective of the study was to develop chili mutant lines with high yield and other superior quality traits through acute and chronic gamma irradiation. The acute irradiation experiment was conducted by exposing seeds of the two varieties to 11 different doses of gamma-ray including 0 (control), 100, 200, 300, 400, 500, 600, 700, 800, 900 and 1000 Gy and it’s were evaluated at M1, M2 and M3 generations. The chronic irradiation experiments were conducted by exposing chili seedlings of the two varieties to various doses of irradiation. The seedlings were kept in ten different rings (Ring 0, 2, 3, 4, 5, 6, 7, 8, 9, 11 and 14) in a gamma greenhouse for 277.2 hours, using Caesium-137 as a source of chronic gamma irradiation at the Malaysian Nuclear Agency, Bangi, Selangor. The accumulated dosage after 277.2 hour of irradiation was 185.61 Gy (Ring 2), 83.11 Gy (Ring 3), 47.096 Gy (Ring 4), 30.474 Gy (Ring 5), 19.4 Gy (Ring 6), 13.9 Gy (Ring 7), 11.1 Gy (Ring 8), 8.31 Gy (Ring 9), 5.54 Gy (Ring 11) and 2.77 Gy (Ring 14). The experiments of acute and chronic gamma irradiation were laid out in a randomized complete block design with three replications under greenhouse facilities at Field 15, Faculty of Agriculture, Universiti Putra Malaysia. In terms of radio-sensitivity, results revealed that the two chili varieties responded differently to various doses of acute gamma irradiation. Mutagenic doses of 310 Gy and 447 Gy were estimated as the LD50 for varieties Chili Bangi 3 and Chili Bangi 5 respectively. The results showed that the M1, M2 and M3 generations of acute and chronic irradiation were significantly different among doses on morphological, physiological and biochemical traits for both chili varieties. Most of the chronic doses stimulated growth and yield characteristics. The relatively moderate doses of chronic gamma irradiation as represented in Ring 4 and 6 were produced mutants with the highest values for all the traits studied. Mutant lines with doses at 100, 200 and 300 Gy had higher mean for most of the traits than control plants. Among acute doses, dose at 100 Gy recorded maximum mean value for the all traits. Both chili varieties shown significantly improvement in traits such as plant height, day to first flowering, chlorophyll a and b, capsaicin content, total phenolic content, fruit length, number of fruits per plant and total yield per plant. In general, both acute and chronic gamma irradiations induced high frequency of visible mutations in both two chili varieties with total mutation frequency 20.23% of 100 and 300 Gy for acute while 12.50% was observed at Ring 4 and Ring 6 for chronic. At M2 and M3 generations, significant increase in number of fruits per plant and total yield per plant was observed among the tall mutant plants (165 - 185 cm) as compared to the parental varieties. Sixteen mutant lines from acute gamma irradiation and 25 mutant lines from chronic irradiation of M3 generation were selected based high yield (>1.8 kg/plant) and number of fruits per plant (>190 fruits/plant) for further evaluation and selection.